A blockchain-based authority management framework in traceability systems. (3rd March 2021) - Li, Jiangfeng; Yu, Yifan; Hu, Shili; Shi, Yang; Zhao, Shengjie; Zhang, Chenxi
The frequent occurrence of product quality and food safety incidents in recent years has greatly lost the trust of consumers. Traceability systems are developed to trace status of products in processes of production, transportation, and sales. However, the tracing data stored in the traceability systems' centralised database can be tampered. In this paper, a blockchain-based authority management framework for traceability systems is proposed. Tracing data are stored on Hyperledger Fabric and interplanetary file system (IPFS) to reduce data storage space and improve data privacy protection on blockchain. In the framework, using the role-based access control (RBAC) mechanism, a blockchain-based RBAC model is presented by defining entities, functions, and rules. Additionally, components in four layers are designed in the framework. Strategies of operation flows are presented to achieve authority management in business applications. The framework not only guarantees the integrity of tracing data, but also prevents confidential information from being leaked. Compared with existing approaches, experiments show that the framework performs better in time and storage.